28 Remote ischaemic conditioning involves signalling via CXCR4 but does not increase circulating levels of its known ligands. (17th November 2015) - Bromage, DI; Pillai, M; Davidson, SM; Yellon, DM
Abstract : Rationale for the study: The CXC chemokine receptor 4 (CXCR4) has been implicated in acute cardioprotection from ischaemia-reperfusion injury conferred by remote ischaemic conditioning (RIC). CXCR4 has two known ligands, namely Stromal Derived Factor-1α (SDF1α) and Macrophage Migration Inhibitory Factor (MIF). We have previously demonstrated that total SDF-1α increases significantly after RIC in a murine model. 1 Using a novel antibody specific to the active form of SDF-1α, we measured circulating SDF-1α and MIF after RIC to ascertain their involvement in RIC. Methodology: In contrast to our previous study, rats were ventilated with supplementary oxygen. Animals were randomly allocated to receive either RIC (3 × 5 min hind limb ischaemia) or sham. Total and active SDF-1α together with MIF were measured in plasma by ELISA. In a separate experiment, healthy, normoxic human volunteers were subjected to RIC (3 × 5 min arm ischaemia), and samples taken for ELISA and FACS analysis of platelet SDF-1α expression. Results: RIC did not significantly affect total SDF-1α in either rats or humans, while active SDF-1α was significantly reduced in human volunteers. MIF was unchanged. RIC did not alter the surface expression of SDF-1α on platelets. Conclusions: Despite our previous finding of increased total SDF-1α after RIC, we found no change of either total or active SDF-1α or MIF after RIC in the present murine study. This may relate to tissue oxygenation and requires further investigation. Active SDF-1α was unexpectedly decreased after RIC in humans. The implications for the role of these two chemokines in RIC still require definition.